Do the Rich Save More in Latin America? - Néstor Gandelman (Inter-American Development Bank (IDB), 2015)
This paper follows two strategies to address whether the rich save more. First, the paper implements a two-stage procedure in which the household's lifetime income is instrumented with the education level of the household head and the education level of his/her partner. Second, using information on home assets, the paper constructs a wealth index. There is evidence that the richest households save more in Argentina, Bolivia, Brazil, Costa Rica, Ecuador, Honduras, Mexico, Panama, Paraguay and Peru. On the other hand, no differences are found in saving rates by lifetime income or wealth in Bahamas, Chile, Colombia and Uruguay.
hdl:11319/6914
Keywords: C81; D12; D14; E21; 330; Saving rates; Two-stage procedures; Median regressions; Latin America